1991
DOI: 10.1002/cyto.990120205
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric measurement of intracellular pH in cultured human keratinocytes using carboxy‐SNARF‐1 and flow cytometry

Abstract: In this study we describe a method to measure intracellular pH in cultured human keratinocytes using flow cytometry. Keratinocytes pose a technical problem because the population is heterogeneous with respect to size and metabolic activity (nonspecific esterase activity), resulting in variability in dye uptake. In order to compensate for this, dyes were selected that change colour with pH. The ratio of fluorescence intensities at two wavelengths was recorded and used as a measure of intracellular pH by referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 15 publications
(13 reference statements)
2
43
0
Order By: Relevance
“…6. This result is in agreement with those obtained by Van Erp et al (1991) and Martinez-Zaguilan et al (1991).…”
Section: Ph Measurements On Single Cells Using Dual Emission Detectionsupporting
confidence: 93%
“…6. This result is in agreement with those obtained by Van Erp et al (1991) and Martinez-Zaguilan et al (1991).…”
Section: Ph Measurements On Single Cells Using Dual Emission Detectionsupporting
confidence: 93%
“…The cell concentration was 1 x 106 cells ml-'. We used the fluorochrome carboxy-seminaphthorhodafluor-1 (C-SNARF-1) as the pH probe for our flow cytometry measurements (Bassnett et al, 1990;van Erp et al, 1991;Seksek et al, 1991). Its absorption spectrum is pH dependent, such that, once calibrated, the ratio of the absorbances at 575 and 640 nm gives an indication of the pHi as individual cells are analysed in the flow cytometer.…”
Section: Intracellular Ph Determinationmentioning
confidence: 99%
“…From preliminary studies it was clear that leakage of this probe was negligible (data not shown), as was mentioned by Van Erp et al (13). Calibration of the cytosolar pH has been performed using high K + buffers with different pHs and nigericin (2 kg/ml) as the proton ionophore.…”
Section: Resultsmentioning
confidence: 74%